DEMANDS FOR INDIGENOUS HEALTH AT THE 16th NATIONAL HEALTH CONFERENCE (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
In this work, we retrieve the historical path of the construction of health policy for indigenous peoples, in addition to identifying what are the main demands presented by the indigenous and / or indigenous health professionals who were present at the 16th National Health Conference. Based on the Report of this Conference we observed the proposals of the indigenous populations in the three axes, in addition to making the theoretical effort to understand the reality of these demands. The proposals present the need to strengthen policy management, strengthening programs such as Mais Médicos, need for permanent professional staff, physical structure, human resources, research, participation and social control, financing, strengthening traditional practices, attention to mental health and preventive health, among others. It is evident that the reality of indigenous peoples is extremely challenging and requires the State to be effective in providing health care to these peoples, but we must not forget the defense of territory and culture.